The National Direct-Drive Inertial Confinement Fusion Program. (18th December 2018) - Regan, S.P.; Goncharov, V.N.; Sangster, T.C.; Campbell, E.M.; Betti, R.; Bates, J.W.; Bauer, K.; Bernat, T.; Bhandarkar, S.; Boehly, T.R.; Bonino, M.J.; Bose, A.; et al.
Abstract: The National Direct-Drive Inertial Confinement Fusion Program consists of the 100 Gbar Campaign on the 30 kJ, 351 nm, 60-beam OMEGA Laser System and the megajoule direct-drive (MJDD) Campaign on the 1.8 MJ, 351 nm, 192-beam National Ignition Facility (NIF). The main goals of the 100 Gbar Campaign are to demonstrate and understand the physics for hot-spot conditions and formation relevant for ignition at the MJ scale, while the MJDD Campaign seeks to understand the laser plasma interactions, energy coupling, and laser imprint for ignition-scale direct-drive coronal plasmas. An overview of the multiyear, systematic effort that is underway for the National Direct-Drive Inertial Confinement Fusion Program (including laser, target, and diagnostic improvements in progress), as well as recent results from the 100 Gbar Campaign on OMEGA and the MJDD Campaign on NIF is presented in this paper.